Penyesuaian Diri dan Coping Strategy pada Pekerja Seks Komersial yang Terinfeksi Infeksi Menular Seksual - Putu Tania Lita Devi; Supriyadi Supriyadi (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Worked as commercial sex workers is very close to a variety of risks as a consequence, one of them is infected with a sexually transmitted infections. The impact of the disease can affect the sex workers from physical and psychological, so they need an adjustment to be able to adjust to the situation and their environment. Positive adjusment requires something named coping strategy, coping strategy is divided into two, first called emotional focused and second called problem focused coping. This study aims to research the relationship between adjustment and coping strategy in commercial sex workers infected sexually transmitted infections.Subjects in this study were 87 commercial sex workers in Denpasar area, between the age 20-55 years old. The instrument of this research is the scale of adjustment and scale of coping strategy that has been tested for validity and reability, the scale of adjusment value rxx = 0,977 and scale of coping strategy value rxx = 0,934.Results of Pearson’s product moment correlations show a correlations of 0,655 with a significants level 0,000 indicates there’s positive relationship between the adjustment to the coping strategy, while the R2 value of 0,429 indicates that the variable can explain the variable adjustment to variable coping strategy by 42,9%. Keywords: Adjusment, Coping Strategy, Sexually Transmited Infections, Commercial Sex Workers.